Grammatical Cohesion Analysis in the Short Story “The Devoted Friend” by Oscar Wilde - Kadek Novi Krisna Dewi; Gede Irwandika (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2024)
This study examined about grammatical cohesion that applied in the short story “The Devoted Friend. The aims of the research is to identify the different forms of grammatical cohesiveness and their applications in the short narrative "The Devoted Friend." The descriptive qualitative method was used to analyze the data. The study's findings were communicated both formally and informally. The data was taken from Oscar Wilde's short story "The Devoted Friend," and it was examined using Halliday and Hasan's (1976) cohesion theory to look at the various forms of grammatical cohesion and how they are used.  The results indicate that the short story uses two different forms of grammatical cohesion: conjunction and reference. Within the short story "The Devoted Friend," there are three different kinds of references: demonstrative, comparative, and personal. There are three different kinds of conjunctions: causal, adversative, and additive conjunctions. The most prevalent type of grammatical cohesion in the short story is personal reference occurs 124 times, whereas comparative reference occurs 13 times, making it the least frequently occurring type.